Experimental Study on Damage and Failure of Coal-Pillar Dams in Coal Mine Underground Reservoir under Dynamic Load - Qiangling Yao; Liqiang Yu; Ning Chen; Weinan Wang; Qiang Xu (Geofluids)
The stability of coal-pillar dams in underground hydraulic engineering works is affected not only by long-term water erosion but also by dynamic loading induced, for example, by roof breaking or fault slipping. In this paper, the water absorption characteristics of coal samples from western China were studied by nondestructive immersion tests, and a high-speed camera was used to monitor SHPB tests on samples of varying water content and subjected to various strain rates. Besides, the coal-pillar dam is numerically simulated based on the experimental data and the actual engineering conditions. The results show that, given low strain rate and high water content, the compaction stage accounts for most of the stress-strain curve, whereas the elastic stage accounts for only a relatively small fraction of the stress-strain curve. The dynamic compressive strength and elastic modulus follow exponential and logarithmic functions of strain rate, respectively, exhibiting a significant positive correlation. As the water content increases, the dynamic elastic modulus increases almost linearly, and the compressive strength decreases gradually. Under the same impact load, samples with greater water content fail more rapidly, and the failure is exacerbated by the propagation of parallel cracks to staggered cracks. The average size of coal fragments decreases linearly with increasing strain rate and water content. Simulations indicate that dynamic loading increases the stress concentration on both sides of the dam and expands the high-stress area and plastic zone. The results provide guidance for designing waterproof coal pillars and underground reservoir dams.